Neuroprogression in psychiatric disorders - Halaris, Angelos; Leonard, Brian Edmund 1936- (Modern trends in pharmacopsychiatry / series editor B.E. Leonard, 2017)
In this volume, international experts critically review cutting-edge advances in neuroprogression research. The relevance of these findings to psychiatric and neurological disorders is clarified. Potential etiopathological mechanisms of neuroprogression are described in detail. Special emphasis is placed on the role of the immune system in stress and stress-related disorders and brain-immune interactions. The epigenetic consequences of adverse experiences in early childhood, which may prelude major psychiatric disorders, are also considered. Recent research has not only provided evidence of neuroprogression in psychiatric and neurological disorders, but has shown that pharmacologic interventions have the potential to arrest this process. Advances in testing and imaging will lead to timely diagnosis and earlier treatment. Identification of neurological mechanisms alongside (epi-)genetic vulnerability markers will create truly personalized treatment programs. This book is a valuable resource for everyone who wishes to gain insight into the essential features of the neuroprogressive course of major psychiatric and neurological disorders. In particular, psychiatrists, neuroscientists and neurologists -as well as immunologists, pharmacologists and molecular biologists- will find very informative chapters of direct relevance to their field.